The Reasoning By Nodding For Ibn Ashur Through Liberation And Enlightenment (Surat Al-Nur) As A Model - Samim Siddiq, Rana (International Journal of Psychosocial Rehabilitation, 2020)
Reasoning by nodding is one of the methods of proving the proper description of the ruling, as it is one of the paths of the bug that the diligent deliberately seeks to extract the illness from the text to reach the appropriate judgment It is a deductive mental process of utmost importance in the work of analogy, especially in the cause of investigation. Surat Al-Nur included among the purposes often related to the provisions of the cohabitation of men with women and the etiquette of mixing and visiting, so it was the share of what the nodding involved in these rulings: the limit of adultery, the punishment of those who spit on the women in marriage, the provisions for curse, and the rulings for seeking permission to enter the inhabited houses of people and enter the houses of others inhabited. It was an applied model in explaining by gestures through the book of Tafsir: Al-Tahrir and Enlightenment by Ibn Ashour, which included many benefits and kindness while being keen to touch the wisdom and the occasions of the provisions and legislation.